EVALUATION OF EARLY AND LONG TERM RESULTS OF THE TREATMENT OF MUCOCELE OF THE LIP USING 980 NM DIODE LASER - Qafmolla, Alketa; Bardhoshi, Merita; Gutknecht, Norbert; Bardhoshi, Esat (European Scientific Journal, ESJ, 2014)
The objective The objective of this study is to compare the results obtained from treatment of mucocele with cold scalpel versus 980 nm diode laser . Introduction : Mucoceles are common benign lesions of the oral cavity that develop following extra vacation or retention of mucous material from salivary glands in the subepithelial tissue.Treatment may be performed by conventional surgery, cryotherapy and more recently laser surgery.Material and methods : In this study we report 20 cases with mucoceles of the lower lip treated in the Dental Clinic of the University of Tirana from January 2007 to January 2011, 10 of them are resected with a scalpel and 10 with 980 nm diode laser.We have documented the operative treatment and postoperative follow-up for each patients for the evaluation of early and long term results. Results : Diode laser surgery was rapid and bloodless.Postoperative period was without complication,after one month from the treatment with laser no scar formation was reported versus the cases treated with scalpel.After 1-3 years of follow-up no recurrence was recorded after laser surgery compared with 3cases of recurrence among the cases of conventional surgical removal of mucocele. Conclusion: 980 nm diode laser is a good modality for the treatment of mucocele´slip.This treatment provides satisfactory results and is also wellaccepted by all age groups .